DISCOURSE ON ZAKAT REGULATION IN THE MANAGEMENT OF ZAKAT IN INDONESIA - Holilur Rahman; Busro Busro (Reflektika, 2020)
This paper argues that the Indonesian government (President, Peoples’ Representative Council/DPR, Ministry of Religious Affairs (MORA), and local   government) has an important role in distributing social welfare to Muslim public (Muslim society) by stipulating official regulations, which authoritize the National Board of Zakat Managers (Badan Amil Zakat Nasional) to manage zakat in Indonesia. We call these regulations “qada’i” (ketetapan negara), while we dub the normative set of laws from the Qur’an and Hadith (utterances ascribed to the Prophet Muhammad) “diyani/obedience).